Thermal Efficient Design of Distributed MemorGenerator for Dual-port RAM Using Unidirectional High-performance IO Standard - B. DAS; M.F.L. ABDULLAH (ASEAN Journal on Science and Technology for Development, 2017)
he distributeddual-port RAM offersthe high-speed data rate transmission for differentmemory access modes such as: busy mode; interrupt mode; JTAG mode; maser mode; slave mode; and sleep mode, at high-frequency operation. The execution of these modes at high-frequency operation increases the on-chip temperature of distributeddual-port RAM. It might short the distribute dual-port RAM forever. Currently, differenttechniques have been reported, but significanton-chip temperature consumption is not reduced for distributeddual-port RAM. In this paper, the thermal-efficiendesign for disributed dual-port RAM was achieved using IO sandard technique. The distributeddual-port RAM was designed using differentIO standardssuch as; LVTTL IO standardand Mobile_DDR IO standard.It was determined that distributeddual-port RAM was operated at 625 MHz high-frequency operation for busy mode, interrupt mode, JTAG mode, mastermode, slave mode, and sleep mode using LVTTL IO standardand Mobile_DDR IO standard.It was observed that for busy mode 53%, for interrupt mode 61%, for JTAG mode 68%, for mastermode 62%, for slave mode 59%, and for sleep mode 76% temperature was reduced when distrbuted dual-port RAM was designed using Mobile_DDR IO stndard compared to LVTTL IO stndard. The designed distributd dual-port RAM using Mobile_DDR IO stndard offerd the thermal efficiendesign solution for differentmemory access modes at high-frequency data rate transmission that provided the low on-chip temperature consumption. The developed distibuted dual-port RAM will be helpful to produce green computing devices.